Game schedule, travel demands and contextual factors influence key game-related statistics among the top European male basketball teams - Sansone, P.; Gasperi, L.; Conte, D.; Scanlan, A. T.; Sampaio, J.; Gómez-Ruano, M. Á. (Journal of Sports Sciences, 2024)
This study examined the effects of game schedule, travel demands and contextual factors on team game-related statistics during a full season. The top 10 teams competing in the 2020-2021 Euroleague basketball season were included where game-related statistics from their respective national competitions and the Euroleague competition were retrieved (761 games). Hierarchical linear regression models were computed to evaluate the effects of distance travelled, game schedule and contextual factors for the previous and current games (league, season phase, opponent level, game outcome, score differential) on key performance indicators (points, shooting, rebounds, assists, turnovers, fouls). Several significant models (p < 0.05) yielded R2 values ranging from 0.05 to 0.22 with small-to-medium effect magnitudes. Analyses revealed significant associations between longer durations separating games and less free-throws being made and between further distances travelled and worse 3-point shooting, more offensive rebounds and more fouls. Regarding contextual factors, favourable outcomes for shooting, assists, steals, fouling and turnovers were significantly associated with team success. Playing higher-level teams and competing in playoffs or finals was associated with several diminished outcomes. These results emphasize the multi-factorial nature of performance in elite European basketball, with game schedule, travel and various contextual factors requiring consideration in developing holistic operational plans for teams.